Information hiding in communication networks : fundamentals, mechanisms, and applications /: fundamentals, mechanisms, and applications. (2016) - Mazurczyk, Wojciech; Wendzel, Steffen; Zander, Sebastian; Houmansadr, Amir; Szczypiorski, Krzysztof
No abstract available